2016
DOI: 10.1038/srep24563
|View full text |Cite
|
Sign up to set email alerts
|

AtSWEET4, a hexose facilitator, mediates sugar transport to axial sinks and affects plant development

Abstract: Plants transport photoassimilates from source organs to sink tissues through the phloem translocation pathway. In the transport phloem, sugars that escape from the sieve tubes are released into the apoplasmic space between the sieve element/companion cell complex (SE/CC) and phloem parenchyma cells (PPCs) during the process of long-distance transport. The competition for sugar acquisition between SE/CC and adjoining PPCs is mediated by plasma membrane translocators. YFP-tagged AtSWEET4 protein is localized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 39 publications
6
75
0
1
Order By: Relevance
“…However, other reports support the previous opinion that sucrose is a ubiquitous transport sugar, and hexoses are usually absent in the phloem stream [54]. Recently, new membrane transporters of sugar, named SWEET (sugars will eventually be exported transporters), have been discovered, which, among others, are involved in the process of phloem loading, together with H + /sucrose symporter [55,56]. It was shown that AtSWEET4 overexpression increased the size of A. thaliana rosette leaves.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, other reports support the previous opinion that sucrose is a ubiquitous transport sugar, and hexoses are usually absent in the phloem stream [54]. Recently, new membrane transporters of sugar, named SWEET (sugars will eventually be exported transporters), have been discovered, which, among others, are involved in the process of phloem loading, together with H + /sucrose symporter [55,56]. It was shown that AtSWEET4 overexpression increased the size of A. thaliana rosette leaves.…”
Section: Introductionsupporting
confidence: 49%
“…It was shown that AtSWEET4 overexpression increased the size of A. thaliana rosette leaves. In contrast, knock-down of AtSWEET4 (by RNAi) reduced plant growth and decreased chlorophyll content in the leaves [56]. Sugars (sucrose) have been found to affect the activity (and expression) of both the sucrose transporters, which are essential for the efficient transport of sugar over long distances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic work has implicated both a Clade II and a Clade IV SWEET in the germination of Arabidopsis seeds [31,32]. We show here that several PsSWEET gene family members are strongly expressed in germinating pea seeds with PsSWEET5b (a Clade II SWEET ) very strongly expressed within 4 hpi and PsSW17 (a Clade IV SWEET ) strongly up-regulated during germination.…”
Section: Discussionmentioning
confidence: 55%
“…Transgenic analysis has indicated that SWEET s may be activated during seed germination. Seeds over-expressing AtSWEET16 (a Clade IV SWEET ) germinated faster than controls [31] as did those over-expressing AtSWEET4 (a Clade II SWEET ) [32]. However, the expression of endogenous SWEET s during germination has yet to be shown.…”
Section: Introductionmentioning
confidence: 99%